Time utilization and perceived psychosocial work environment among staff in Swedish primary care settings - Eva Anskär; Malou Lindberg; Magnus Falk; Agneta Andersson (BMC, 2018)
Abstract Background Over the past decades, reorganizations and structural changes in Swedish primary care have affected time utilization among health care professionals. Consequently, increases in administrative tasks have substantially reduced the time available for face-to-face consultations. This study examined how work-time was utilized and the association between work time utilization and the perceived psychosocial work environment in Swedish primary care settings. Methods This descriptive, multicentre, cross-sectional study was performed in 2014-2015. Data collection began with questionnaire. In the first section, respondents were asked to estimate how their workload was distributed between patients (direct and indirect patient work) and other work tasks. The questionnaire also comprised the Copenhagen Psychosocial Questionnaire, which assessed the psychosocial work environment. Next a time study was conducted where the participants reported their work-time based on three main categories: direct patient-related work, indirect patient-related work, and other work tasks. Each main category had a number of subcategories. The participants recorded the time spent (minutes) on each work task per hour, every day, for two separate weeks. Eleven primary care centres located in southeast Sweden participated. All professionals were asked to participate (n = 441), including registered nurses, primary care physicians, care administrators, nurse assistants, and allied professionals. Response rates were 75% and 79% for the questionnaires and the time study, respectively. Results All health professionals allocated between 30.9% - 37.2% of their work-time to each main category: direct patient work, indirect patient work, and other work. All professionals estimated a higher proportion of time spent in direct patient work than they reported in the time study. Physicians scored highest on the psychosocial scales of quantitative demands, stress, and role conflicts. Among allied professionals, the proportion of work-time spent on administrative tasks was associated with more role conflicts. Younger staff perceived more adverse working conditions than older staff. Conclusions This study indicated that Swedish primary care staff spent a limited proportion of their work time directly with patients. PCPs seemed to perceive their work environment in negative terms to a greater extent than other staff members. This study showed that work task allocations influenced the perceived psychosocial work environment.